An ultrastructural abnormality of neutrophils presenting with impaired function - Yeğin, Olcay; Aşan, Esin; Örs, Ülken; Yetgin, Sevgi; Ciliv, Gönenç; Berkel, A. İzzet (The Turkish Journal of Pediatrics, 1988)
Polymorphonuclear neutrophils (PMN) from a patient with recurrent infections were found to have ultrastructural abnormalities and impaired functions. The PMNs had atypical cytoplasmic granule-like structures, increased surface ruffling and rudimentary pseudopodia formation. Close relation to the Golgi complex, fusion with phagocytic vacuoles and rapid disappearance after phagocytosis suggest that these atypical structures are related to the granules. Ultrastructurally, both the primary and secondary granules were present in the patient’s PMNs. Myeloperoxidase staining, lysosomal enzyme levels of primary granules and alkaline phosphatase activity of PMNs were found to be normal. The PMNs were impaired in chemotaxis and bactericidal capacity. This data indicates a new intrinsic PMN defect which may be responsible for the increased susceptibility of our patient to pyogenic infections.